Kinetics and Mechanism of Oxidation of Formaldehyde with Bi(V) in HClO4-HF Mixture - Jha, C.S.; Kumar Jha, Vijay; Jha, Sushil; Mohan Mishra, Prem (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of formaldehyde with Bi(V) fluoride complex have been investigated in HCIO4-HF mixture. The reaction is first order in each reactant. Hydrogen ion and ionic strength (HP) and added fluoride (F- ) have no effect on the reaction rates. The mode of electron transference for the substrate (HCOOH) to the oxidant [Bi(V)] has been indicated via. a bridged outer sphere mechanism.